Seismic performance of precast concrete-filled circular tube segmental column under biaxial lateral cyclic loadings - Li, C.; Hao, Hong; Bi, Kaiming (Springer, 2018)
Precast segmental column has been developed in recent years as one of the widely used prefabricated structures to accelerate construction speed. However, its applications are limited in the areas of low seismicity due to insufficient knowledge about its performance under seismic loading. Recently, some research works have been performed to understand the seismic performance of precast segmental columns. However, only the uniaxial cyclic loading was considered. In reality, the seismic excitation is not uniaxial. Considering responses of columns to uniaxial loading only may not accurately reflect the true structural response during an earthquake. In this study, comprehensive numerical analyses are carried out to investigate the seismic performances of circular precast segmental columns under biaxial lateral cyclic loadings. A three-dimensional numerical model is firstly developed and validated against the experimental results of a precast concrete-filled tube segmental column under uniaxial cyclic loading. Six biaxial cyclic loading cases are then applied to the validated model. The numerical results indicate that biaxial cyclic loading paths can significantly influence the strength, ductility and energy dissipation of the column. In addition, the residual displacement of the segmental column increases obviously under biaxial cyclic loading compared with that of the column under uniaxial cyclic loading. Shape memory alloy is found to be effective to minimize the residual displacement of the segmental column under biaxial loading. Moreover, the axial loading ratio has a more pronounced effect on the strength degradations of the column under biaxial lateral cyclic loading than that of the column under uniaxial loading.